WTO disciplines on agricultural support update: evaluation of Japanese agricultural policy reforms under the WTO agreement on agriculture: WTO domestic support update - Godo, Yoshihisa; Takahashi, Daisuke (2012)
This is a WTO domestic support notification update prepared for the International Food Policy Research Institute (IFPRI) on the chapter for India in WTO Disciplines on Agricultural Support: Seeking a Fair Basis for Trade (Orden, David, David Blandford, and Tim Josling, editors), 2011, Cambridge: Cambridge University Press.